Pill beetles (Coleoptera, Byrrhidae) of Kemerovskaya Oblast, Russia - Efimov, D. A. (Евразиатский энтомологический журнал)
A preliminary list of 11 Byrrhidae beetle species from 6 genera collected from Kemerovskaya Oblast of Russia is presented. Nine species are newly recorded for the fauna of Kemerovskaya Oblast. Presence of relic mountain species in combination with residents of steppes and widespread forest species characterize high diversity of the regional fauna and determine necessity of further study of local species distribution.